Identidade e atuação do pedagogo na educação profissional: um olhar para o Instituto Federal de Educação, Ciência e Tecnologia de São Paulo - IFSP - Arruda, Tathiane Cecília Enéas de (2022)
The theoretical research presents as a central problem, to understand to what extent the pedagogue can resignify its identity and its performance in an institution of Vocational Education and what activities it can carry out, aiming at the improvement and the quality of the pedagogical processes. To this end, it was necessary to go through the historical and legal trajectory of the Pedagogy course from 1939 to the present day and Professional Education as a teaching modality in the formation of the pedagogue, the emergence of Professional Education and its objectives, listing the main public and technical schools. and their formative paths, as well as the different actions of the pedagogues who work in these institutions, based on document and content analysis. The researched space was the Federal Institute of Education Science and Technology of São Paulo – IFSP Câmpus São Paulo since 1909 as Schools of Apprentices and Craftsmen, the process of expansion of the Professional and Technological Network and impacts on management and roles played by the pedagogues who work there from hiring to joining the institution through a public tender. The thesis has a qualitative approach and theoretical construction based on Franco (2014), Luciano (2022), Masetto (2018), Sacristán (2005) Feldmann (2009), Freitas (2016) Chizzotti (2014) among others. continuing and in-service training course about their actions with a view to improving pedagogical processes, such as: assistance to the policy of permanence and success, academic efficiency of the courses and greater dialogue with teachers. Sacristán (1995) states that psychological and cultural conditions are implicitly linked to professionalism and, therefore, such aspects should be considered in initial and continuing education, in addition to continuing education must be part of the collective's personal and professional development. In the construction and reconstruction of their identity and performance, the thesis proposes that this professional recognizes himself as a mediator, advisor and pedagogical consultant with his peers, especially with teachers, aiming as stated (Feldmann), a “permanent process of appropriation, mediation and transformation of knowledge through an existential and collective project of human construction”